Investigational New Drugs Novel Anti-Cancer Therapeutics and Therapies - Rowinsky, Eric K.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The development of new anticancer agents is one of the most rapidly changing aspects of cancer research. Investigational New Drugs provides a forum for the rapid dissemination of information on new anticancer agents. The papers published are of interest to the medical chemist, toxicologist, pharmacist, pharmacologist, biostatistician and clinical oncologist. Investigational New Drugs provides the fastest possible publication of new discoveries and results for the whole community of scientists developing anticancer agents. Each issue contains original articles dealing with anticancer drug development. Other sections are devoted to invited review articles and letters to the editor. The journal also affords the opportunity to publish the proceedings of special workshops and symposia devoted to the development of new anticancer agents. Provided they add to the understanding of the investigational agents, the journal is not adverse to publishing clinical trials with negative results. Investigational New Drugs cuts across all the usual lines or subdisciplines, providing a locus for the presentation of relevant investigations and the discussion of critical questions appropriate to the entire field of new anticancer drug development.
Keywords: Pharmacology; Oncology; Oncology; Pharmacology/Toxicology.